Pattern of Knowledge Creation on Teaching Effectiveness among Lecturers in Library Schools in Southwest, Nigeria - OSISANWO, Temitope A.; SIMISAYE, Ahmed O.; ADEGBILERO-IWARI, Idowu; AWONUSI, Solomon O. (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This study examines the impact of knowledge creation practices on the teaching effectiveness of lecturers in library schools across Southwest Nigeria. Despite the crucial role of education in national development, ineffective teaching and limited knowledge creation hinder progress in library schools. Using a descriptive survey design and total enumeration, data were collected from all 159 lecturers that constituted the study population across 17 institutions offering library and information science in southwest, Nigeria through a structured questionnaire. Findings indicate a significant positive relationship between knowledge creation and teaching effectiveness. Lecturers who engaged in collaborative research, developed innovative instructional methods, and integrated knowledge creation into their teaching achieved better student outcomes. However, barriers such as inadequate funding, limited resources, and weak institutional support restricted effective knowledge creation. The study highlights the need to embed knowledge creation within teaching frameworks to enhance educational quality. It recommends increased investment in professional development, improved resource allocation, and institutional policies that prioritise knowledge creation. Strengthening these areas will help library schools align with global educational standards and better equip graduates for real-world challenges.